Metembing traditional games: an ethnographic study of its practice and preservation - Ni Wayan Pujasari; Made Agus Wijaya; Ni Luh Putu Spyanawati (Universitas Sriwijaya, 2025)
Research Problems: The lack of literature studies, such as books discussing traditional metembing sports in elementary education units, is the root of this problem and the socialisation of traditional sports games. Research Objectives: This study aims to describe the Traditional Metembing Sports Game in Baha Tourism Village, Badung Regency. Methods: This study uses a qualitative method with an ethnographic approach. Data collection techniques use observation, interview, and documentation techniques. The research instrument uses interview guidelines. Results: The results of this study are from 5 informants who were interviewed, they know the traditional metembing sports game, but if implemented in schools, many students do not know this traditional sports game, therefore the development of traditional metembing sports games among the younger generation is almost unknown due to the lack of literature and lack of socialization of traditional sports games. Conclusion: The traditional metembing sports game is a hereditary heritage from Baha Tourism Village, Mengwi District, Badung Regency, which is played as entertainment to fill free time. The facilities and infrastructure used are in the form of broken roof tiles and coins. The characters developed in this traditional metembing sports game are the values of honesty, hard work, sportsmanship, and discipline. Meanwhile, the prominent physical fitness components in the traditional metembing sport are accuracy, coordination, and flexibility. This study provides in-depth information about the traditional metembing sport, which is still oral. It is hoped that traditional sports will get a balanced proportion in the elementary and secondary education curriculum.